Pengaruh Penerapan Model Pembelajaran Siklus Belajar Pada Mata Pelajaran Pendidikan Agama Kristen terhadap Tanggung Jawab Siswa Kelas 6 Sekolah Dasar Kristen Gamaliel Makassar - Ricky Putra Gala (Jurnal Ilmiah Wahana Pendidikan, 2021)
The learning cycle method consists of 5 phases, namely exploring, planning, doing, communicating and reflecting. The purpose of implementation of this learning cycle method for students in the grade 6 of Gamaliel Makassar Elementary School is to influence students become responsible for whatever is entrusted to them. This quantitative research uses a research and development (R&D) approach with data collection techniques such as questionnaires and interviews with teachers and literature studies through scientific books, research reports, scientific essays, theses and dissertations, encyclopedias, and other sources by written or other electronic sources. Then, the data was analyzed using a rating scale. This research had taken place at Gamaliel Elementary School Makassar and the object of research is the students of grade 6A. The research variable consists of dependent variable namely the student's responsibility, and the independent variable namely the learning cycle method. From the results, it was concluded that the learning cycle method was very appropriate to be used to train students' responsibility at the Gamaliel Elementary School Makassar. This is proved by the observations that students try to do assignments from the teacher independently without plagiarizing from friends, behave in an orderly manner in class, maintain cleanliness and carry out picket duties in class with responsibility.